Analisis Strategi Pemasaran Produk KUR PT BNI Cab. Tanjung Pinang - Syafyeni, Alber; Azman, Heru Aulia (CV. ITTC INDONESIA, 2025)
In order to provide support for the development of MSMEs, the Government of the Republic of Indonesia is collaborating with BNI to distribute People's Business Credit (KUR). For the 2023 budget year, BNI received a target allocation for KUR distribution of IDR 36.5 trillion. In order to optimize the absorption of the National KUR ceiling and pay attention to the achievement of BNI's KUR distribution performance, it has been decided that the BNI KUR distribution target will be IDR 18 trillion according to the Letter of the Coordinating Ministry for the Economy of the Republic of Indonesia No. B/PK.KUR/153/D.I.M.EKON/09/2023 dated September 25, 2023. The objectives of this study are (1) to determine the strengths and weaknesses of BNI tjg pinang in increasing the market share of KUR products for opportunities and threats (2) To formulate marketing strategies in increasing the market share of KUR products. This study uses a qualitative descriptive method using field research, namely research conducted in the field in the real scene. Through the research results, it is known that Based on the results of the EFAS Analysis, it is known that the main opportunity for Bank BNI Tanjung Pinang branch lies in the attribute of Government support for the development of MSMEs with a score of 4.861953, then the second and third attributes have the same score of 4.609428, these attributes are the increasing needs of the community for KUR products and Having cooperation with Bank Agents, Cooperatives, farmer/fisherman groups and others. Furthermore, the results of the study related to the threat from the external environment, the highest assessment is in the attribute of the similarity of strategies used with other competitors with a score of 0.942761. Next is the change in rules/provisions from the local or central government 1.87991 then the third highest assessment is in the attribute of wide marketing area coverage with a score of 1.523008. Thus, the same marketing strategy is a real threat which is an external factor that must be watched out for. Based on the Cartesian SWOT diagram, the results show that Bank BNI Tanjung Pinang branch is currently implementing an important strategy to minimize risk by spreading funds to various instruments. This strategy helps reduce dependency, increase profits, and increase knowledge.